Efficacy and safety of ciprofol for the induction of general anesthesia in patients with obesity undergoing laparoscopic sleeve gastrectomy: A double-blind randomized, controlled study - Xiaowei Chi; Yi Xu; Qiang Li; Keshu Xia; Qiang Fu (PLoS ONE, 2025)
Background The selection of safe and effective anesthetic agents for patients undergoing bariatric surgery is vital. This study aimed to evaluate the efficacy and safety of ciprofol in inducing general anesthesia in patients with obesity undergoing laparoscopic sleeve gastrectomy. Methods A total of 212 patients scheduled for laparoscopic sleeve gastrectomy were randomly allocated into two groups in a 1:1 ratio: the ciprofol (0.5 mg/kg, n = 106) and propofol (2.5 mg/kg, n = 106) groups. The primary endpoint was to assess the success rate of anesthesia induction. Secondary endpoints included evaluating the time of induction, loss of eyelash reflex, changes in bispectral index, and adverse event incidence. Results The success rates of anesthesia induction were 100% in both groups. Ciprofol demonstrated non-inferiority to propofol in induction success. The times to successful induction onset and eyelash reflex disappearance were significantly longer in the ciprofol group compared to those in the propofol group (39.38 ± 8.57 s vs. 36.74 ± 6.82 s, P = 0.014 and 40.36 ± 8.59 s vs. 37.77 ± 6.84 s, P = 0.016, respectively). The adverse events incidence was significantly lower in the ciprofol group compared to that in the propofol group (25.47% vs. 89.62%, P = 0.000). The number of patients requiring top-up doses was not statistically significant (3.77% vs. 7.55%, P = 0.235). Ciprofol demonstrated advantages in hemodynamic stability and maintaining a better sedation level post-induction. Ciprofol was associated with a significantly lower incidence of hypotension compared to propofol (14.15% vs. 37.74%, P < 0.001), and more patients maintained appropriate sedation depth (86.80% vs. 72.64%, P = 0.010, 40 ≤ bispectral index ≤ 60 within 10 min of intravenous administration). Conclusion Ciprofol offers a better sedative effect, fewer adverse events, and greater hemodynamic stability during general anesthesia induction in patients with obesity undergoing laparoscopic sleeve gastrectomy. Trial registration ClinicalTrials.gov NCT05522998